2022
DOI: 10.1021/acsenergylett.2c01945
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Compound-Based Electrocatalysts for Hydrogen Peroxide Electrosynthesis and the Electro-Fenton Process

Abstract: Hydrogen peroxide (H 2 O 2 ) is a powerful oxidant with many applications, but its chemical production is unsustainable and unsafe. Decentralized electrosynthesis of H 2 O 2 via the selective two-electron oxygen reduction reaction (2e − ORR) is attractive, which demands active, selective, stable, and cost-effective electrocatalysts in acidic and neutral solutions where H 2 O 2 is stable. Metal compounds are an emerging class of 2e − ORR catalysts with diverse and tunable structural motifs for optimizing H 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…[294][295][296][297] The other is a twostep 2e À transfer route involving the generation of H 2 O 2 (under acidic conditions) or HO 2 À (under alkaline conditions) as the intermediates, which is often used for industrial H 2 O 2 production. [298][299][300][301] Specifically, for the direct 4e À pathway, there are two possible mechanisms with different intermediates involved (associative: O*, OOH*, and OH*; dissociative: O* and OH*) depending on the original O 2 dissociation energy barrier. In general, the ORR activity is governed by both the thermodynamic adsorption energetics of these intermediates and the kinetic energy barriers between different reaction steps.…”
Section: Oxygen Reduction Reaction To Date Proton Exchange Membrane F...mentioning
confidence: 99%
“…[294][295][296][297] The other is a twostep 2e À transfer route involving the generation of H 2 O 2 (under acidic conditions) or HO 2 À (under alkaline conditions) as the intermediates, which is often used for industrial H 2 O 2 production. [298][299][300][301] Specifically, for the direct 4e À pathway, there are two possible mechanisms with different intermediates involved (associative: O*, OOH*, and OH*; dissociative: O* and OH*) depending on the original O 2 dissociation energy barrier. In general, the ORR activity is governed by both the thermodynamic adsorption energetics of these intermediates and the kinetic energy barriers between different reaction steps.…”
Section: Oxygen Reduction Reaction To Date Proton Exchange Membrane F...mentioning
confidence: 99%
“…The indirect mechanism involves a 2e pathway for H 2 O 2 formation and another 2e pathway for water formation. 282,283 The 2e pathway is conducive to H 2 O 2 production. In the ORR process, multiple intermediates are involved, including the reduction and decomposition of O 2 *, as well as the removal of adsorbed O*, HO*, and H 2 O*.…”
Section: Electrocatalytic Applications Of Heasmentioning
confidence: 99%
“…The oxygen reduction reaction (ORR) is an important reaction that can find applications in a variety of fields. The 4-electron (4-e) ORR to H 2 O or OH – are usually used as the cathodic reaction of fuel cell in the energy field. However, it is a green strategy to synthesize multipurpose H 2 O 2 through a 2-electron (2-e) ORR. Moreover, the 2-e ORR has been applied in the electro-Fenton process to deal with organic pollutants. , Recently, it was reported that the ORR could be applied to assist the electrochemical synthesis of metal–organic frameworks (MOFs) on the electrode in the nonaqueous electrolyte. , …”
Section: Introductionmentioning
confidence: 99%
“…4−6 Moreover, the 2-e ORR has been applied in the electro-Fenton process to deal with organic pollutants. 7,8 Recently, it was reported that the ORR could be applied to assist the electrochemical synthesis of metal−organic frameworks (MOFs) on the electrode in the nonaqueous electrolyte. 9,10 MOFs are a new class of porous materials that are formed via the coordination between metal ions and organic ligands.…”
Section: Introductionmentioning
confidence: 99%